Blora Local Wisdom 2D Animation Video-Based Learning Media Development in Improving 5th Grade Students’ Writing Skills - Galih Cahya Pratama; Ali Sunarso; Panca Dewi Purwati (Journal of Primary Education, 2022)
The problem that SDN Bacem 01 Blora facing is the lack of local wisdom-based learning media and students’ poor writing skill. This research aimed to develop 2D animation video based on Blora’s Local Knowledege as a learning media to improve 5th grade students’ ability in writing imaginative text. This research was using Research and Development Method (R&D) with ADDIE (Analysis, Design, Develoment, Implementation, and Evaluation) as the development procedures. The sample of this research was 5th grade students’ of SDN Bacem 01 Blora and SDN Bacem 02 Blora. Questionnaires consisted of media expert, materials expert, teachers’ response, observers’ response, and students’ response were the tools to obtain the data needed. The results of this research gained 93% of media expert, 96% of materials expert, 87% of teachers’ response, 89% of observers’ response, and 82% of students’ response. In conclusion, 2D animation video-based media development was feasible to be utilized to improve students’ ability in writing imaginative text based on Blora’s local wisdom.